2020
DOI: 10.1088/1674-1056/abbbdb
|View full text |Cite
|
Sign up to set email alerts
|

Collective modes of Weyl fermions with repulsive S-wave interaction*

Abstract: We calculate the spin and density susceptibility of Weyl fermions with repulsive S-wave interaction in ultracold gases. Weyl fermions have a linear dispersion, which is qualitatively different from the parabolic dispersion of conventional materials. We find that there are different collective modes for the different strengths of repulsive interaction by solving the poles equations of the susceptibility in the random-phase approximation. In the long-wavelength limit, the sound velocity and the energy gaps vary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The detailed overlap factor has introduced in our previous article. [25] From the expression of the overlap factor, we can find that the 4 × 4 matrix can be written as four 2 × 2 block matrices, where all elements of the two off-diagonal 2 × 2 matrices have e φ or e −φ . The integrals of these elements equal zero with respect to the momentum 𝑘 as the azimuth angle φ runs from 0 to 2π.…”
Section: Theoretical and Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The detailed overlap factor has introduced in our previous article. [25] From the expression of the overlap factor, we can find that the 4 × 4 matrix can be written as four 2 × 2 block matrices, where all elements of the two off-diagonal 2 × 2 matrices have e φ or e −φ . The integrals of these elements equal zero with respect to the momentum 𝑘 as the azimuth angle φ runs from 0 to 2π.…”
Section: Theoretical and Numerical Resultsmentioning
confidence: 99%
“…[19][20][21][22][23][24] We have investigated the collective modes near the single Weyl node model with repulsive S-wave interaction for type-I Weyl fermions. [25] In order to lay the foundation for important applications of Weyl fermions to quantum simulation as well as information technologies in future, it is necessary to study the collective excitations for type-II Weyl fermions in ultracold atom gases.…”
Section: Introductionmentioning
confidence: 99%
“…The heterogeneity of reported clinical assessments and outcomes in case reports [29,34,37] and small studies [19,36], outcome measures and time recorded as well as the variability of reported HBOT protocols [40], makes it difficult to comment about the HBOT therapeutic impact in AD. The studies to date have indicated that one course of HBOT only temporarily ameliorates cognitive impairment in AD patients [36] and the effects may not be permanent.…”
Section: Discussionmentioning
confidence: 99%
“…were observed in COPD patients, and the vascular component of airway remodelling was positively linked to the bronchial expressions of VEGF and TGF-β (Ding et al, 2020). Moreover, loss of VEGF led to endothelial cell apoptosis and resulted in the disappearance of lung tissue in COPD (Soltani et al, 2016 Other prostaglandins, such as prostaglandin E 2 (PGE 2 ), are involved in the VEGF-mediated responses in COPD (Wang et al, 2020). PGE 2 is released in high amounts by the COPD fibroblasts and has been shown to induce VEGF via the PGE 2 receptor E-prostanoid 2 and cAMP activation (Bonanno et al, 2016).…”
Section: Discussionmentioning
confidence: 99%